Cooperation or Confrontation? Assessing the American ‘Pivot’ to Asia in Context – Is It a Western ‘Neo-Liberealism’ Response to China’s New ‘Open Door’ Approach to Europe? - Jones, David A. (Overcoming Controversies in East Asia, 2017)
Much attention has surrounded ‘America’s Pivot to Asia’, hyped in fanfare, castigated by China, welcomed by smaller Asian states in the context of wishful maritime security, all involving an air and naval pivot to Asia by the United States. Less attention has focused on a Western economic pivot to Asia, a significant American financial presence, including World Bank (WB) cooperation under American leadership with the Asia Infrastructure Investment Bank (AIIB) under Chinese leadership. Although the AIIB stands to become theoretically an antithesis of the WB, recently the AIIB changed course quietly, grounding its funding in US dollars instead of Chinese RenMinBi, itself borrowing from the WB to support derivative loans from the AIIB to developing nations! This chapter addresses the significance of what appears facially to be a ‘carrot and stick’ approach, focusing particularly on opportunities for Sino-American and Sino-European cooperation instead of confrontation, then forecasting ways such cooperation will promote progressive military de-escalation. Is this financial cooperation a form of 21st century ‘Dollar Diplomacy’ that will result in an American military pivot away from Asia? If so, it contains some hallmarks of what some might consider ‘Structural Liberalism’ or neo-liberalism in a neo-realist package, possibly to be labeled ‘neo-liberealism’.